Desempenho do Pediatric Asthma Quality of Life Questionnaire adaptado em pacientes com bronquiolite obliterante - Moura, Angela de (2016)
Objective: To evaluate the performance of the Paediatric Asthma Quality of Life Questionnaire Adapted in patients with bronchiolitis obliterans. Methods: The Paediatric Asthma Quality of Life Questionnaire (PAQLQ) adapted was applied, through interviews, in patients diagnosed with bronchiolitis obliterans Post-infectious (BO) and asthma, aged 8 and 17, who were monitoring in a specialized pediatric pulmonology outpatient clinic in Porto Alegre, Brazil. To evaluate the performance of the questionnaire were studied the psychometric properties: Reliability and Validity. The reliability was evaluated by internal consistence measuring the coefficient α Cronbach (α-C). The validity through convergent validity, determining specific correlations between total score and domains and lung function Divergent validity was assessed by the difference between the average domains and total score of the questionnaire of patients with BO and Asthma. The ceiling and floor effects were also evaluated. Results: The study included 41 patients diagnosed with BO and 41 patients with asthma. The average age of the groups was 11.8 ± 2.3 and 66 (81%) of the patients were patients with male sex. The BO showed significantly lower values of pulmonary function to subjects with asthma (P <0.001). In relation to the average reliability Cronbach's alpha coefficient was 0.923 (0.870 to 0.961) .The correlations were strong and significant (P <0.001) between the domains and the overall score, suggesting an acceptable convergent validity. However, the correlations between the domains and total score with lung function were not found and not significant. It was not observed statistical differences and clinically relevant between the average of the areas and the overall score between groups, a similar score in the media among patients with asthma and patients with BO shows that both subjectively presented a good quality of life. Unidentified ceiling or floor effects in the fields and in the total score. Conclusion: Paediatric Asthma Quality of Life Questionnaire Adaptade proved to be a valuable tool in assessing the quality of life of patients with bronchiolitis obliterans, despite being a specific instrument for assessing Related Quality of Life Health of patients with asthma.